Natural cellulose element derived ceramic matrix composite material and preparation method thereof
By dissociating and strengthening natural cellulose elements and growing zirconia ceramic layers in situ on their surface, recombining them into ceramic-based composite materials with natural layered interlocking structures, the application of natural materials in production and life is solved. The problem limits the material to achieve high performance and wide application.
Patent Information
- Application Number
- CN202411467912.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to prepare natural materials with fine microstructures on a large scale, resulting in limited application in production and life.
By dissociating the natural cellulose matrix into basic constituent units and growing the zirconia ceramic layer in situ on its surface, the suction filter directional assembly method is used to recombinate it into a ceramic matrix composite material with a natural layer-like interlocking structure.
The prepared material has similar flexural strength to natural coconut shells, and has higher modulus, hardness and excellent flame retardant properties due to the presence of zirconia, which solves the problem of dimensional limitations and performance loss of natural materials.
Smart Images

Figure CN119427503A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of bionic ceramic-based composite materials, and in particular relates to a natural cellulose-based element-derived ceramic-based composite material and a preparation method thereof. Background Art
[0002] Most natural materials in nature produce fine microstructures during their growth and development. From a microscopic perspective, they are composed of micro-nano basic components assembled in a certain ordered structure. These fine structures give natural materials excellent mechanical and biological properties. For example, the nacre layer of shells is composed of layers of aragonite flakes and organic matter. The fine structure greatly improves its toughness, far exceeding that of artificially synthesized materials. However, due to reasons such as size, processing difficulty and some performance defects, these excellent natural materials are often not directly used in production and life.
[0003] With the development of bionics, many studies are devoted to imitating the microstructure of natural materials. Various directional assembly methods have been developed to manufacture materials with special ordered structures, trying to make materials with adjustable size and performance. However, the finest structures of natural materials are often at a scale of several nanometers or even finer, which makes it difficult to prepare them on a large scale artificially. Summary of the invention
[0004] In view of the above technical problems, the purpose of the present invention is to provide a natural cellulose-based element-derived ceramic-based composite material and a preparation method thereof. The material prepared by the method can solve the shortcomings of natural materials such as size limitation and performance deficiency, and can expand the application of natural materials.
[0005] In a first aspect, the present invention provides a natural cellulose element-derived ceramic-based composite material, wherein the natural cellulose element-derived ceramic-based composite material has a layered structure formed by alternating stacking of cellulose elements formed by dissociation of natural materials and zirconium oxide ceramic layers of reinforcing materials formed in situ on the surface of the cellulose elements; the layered structure presents a natural layered interlocking structure similar to that of natural cellulose elements before dissociation; The source of the cellulose base element includes plant shells; the zirconia ceramic layer includes crystalline zirconia, amorphous zirconia and crystalline-amorphous zirconia composite; The mass proportion of the natural cellulose unit is 80-20%, and the mass proportion of zirconium oxide is 20-80%.
[0006] Preferably, in the natural cellulose element-derived ceramic-based composite material, the length of the cellulose element is 50-200 um, and the width and thickness are both 10-50 um; and the thickness of the zirconia ceramic layer is 1-20 μm.
[0007] Preferably, the natural cellulose-based ceramic-based composite material has a flexural strength of 60 to 110 MPa, a modulus of 5 to 20 GPa, and a fracture toughness of 1 to 3 MPa·m 1 / 2 , tensile strength is 10~50MPa, and hardness is 0.2~1.5GPa.
[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned natural cellulose-based element-derived ceramic-based composite material, the preparation method comprising the following steps: (1) placing plant shell fragments in a delignification solution containing sodium chlorite, and subjecting them to heat treatment and washing to obtain a natural cellulose base solution; (2) mixing the natural cellulose element solution with the zirconium oxychloride octahydrate solution, stirring, adjusting the pH, and reorganizing the element structure to obtain a natural cellulose element-derived ceramic-based composite material body; (3) subjecting the obtained natural cellulose-based element-derived ceramic-based composite material body to low-temperature hot pressing to obtain the natural cellulose-based element-derived ceramic-based composite material.
[0009] Preferably, in step (1), the concentration of sodium chlorite in the delignification liquid containing sodium chlorite is 5 to 30 wt%, preferably 10 to 20 wt%.
[0010] Preferably, in step (1), the concentration of the natural cellulose base solution is 1 to 50 g / L, preferably 2.5 to 5 g / L.
[0011] Preferably, in step (2), the mass ratio of the natural cellulose unit to the theoretically generated zirconium oxide is 1:(0.25-4), preferably 1:1.
[0012] Preferably, in step (2), ammonia water is added to adjust the pH, the concentration of the ammonia water solution is 0.2-2 wt%, preferably 0.5-1 wt%, and the pH value of the mixed solution is controlled to be 10-12.
[0013] Preferably, in step (2), the method for reorganizing the elementary structure includes suction assembly, evaporation self-assembly, shear force self-assembly, pressure assembly, and ice template method.
[0014] Preferably, in step (3), the temperature and pressure of the low temperature hot pressing are 60-200° C. and 50-500 MPa, preferably 120-160° C. and 150-300 MPa, and the time of the low temperature hot pressing can be 1-24 h.
[0015] Beneficial Effects (1) The present invention dissociates natural materials into their basic components, and after being strengthened by a zirconium coating, assembles them into an original ordered structure by filtration, and prepares a ceramic-based composite material with an original coconut shell structure based on the cellulose unit of the natural coconut shell material. The material has a bending strength similar to that of the natural coconut shell, and due to the presence of zirconium oxide, it has a higher modulus, exhibits a higher hardness, and has excellent flame retardant properties; (2) The present invention utilizes waste materials such as natural coconut shells to prepare a composite material with excellent performance through a dissociation-strengthening-recombination method, develops a new preparation method for the utilization of natural materials, solves its defects such as size limitations, expands the application range of bio-based materials, and provides a model for the preparation of biomimetic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The schematic diagram of the preparation process of the natural cellulose-based element-derived ceramic-based composite material exemplified in the present invention; Figure 2 The SEM images of the cross section and surface of the initial coconut shell used in Example 1, the left image is the cross-sectional structure perpendicular to the coconut shell, and the right image is the surface structure parallel to the coconut shell; Figure 3 The SEM images of the coconut shell cellulose element after dissociation (left picture) and the coconut shell cellulose element after zirconium oxide deposition (right picture) used in Example 1; Figure 4 This is the SEM image of the cellulose base element surface strengthened by the zirconium layer. The proportions from left to right are CSU:ZrO 2 =4:1, 2:1 and 1:1, with element distribution diagram below; Figure 5 CT reconstruction images of the recombinant material CSU@Zr (left) and natural coconut shell material (right) prepared in Example 1; Figure 6 The cross-sectional SEM image and element distribution diagram of the recombinant material CSU@Zr prepared in Example 1; Figure 7 The bending strength comparison diagram of the materials prepared in Example 1 and Comparative Examples 1-4, wherein: CS is the initial natural coconut shell, CSU is the recombinant material of pure coconut shell element, CSU / pZr is the recombinant material of coconut shell element and zirconium oxide ceramic powder, CSU / Zr is the recombinant material of coconut shell element and zirconium oxide grown non-in situ, and CSU@Zr is the recombinant material after the zirconium layer is in situ grown on the surface of the element; Figure 8 It is a comparison diagram of the modulus of the materials prepared in Example 1 and Comparative Examples 1-4; Fig. 9 The cross-sectional SEM images of the materials prepared in Example 1 and Comparative Examples 1-4; Fig.10 This is a comparison chart of the hardness of the materials prepared in Example 1 and Comparative Examples 1-4; Fig.11 This is a comparison chart of the heat release rate (HRR) of the flame retardant test of coconut shell and CSU@Zr. DETAILED DESCRIPTION
[0017] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0018] Research has found that natural materials are often assembled from basic assembly units in a certain ordered structure. Inspired by the assembly unit, the present invention prepares a natural cellulose unit-derived ceramic-based composite material with good performance through a unit dissociation-strengthening-recombination method.
[0019] First, the natural cellulose element-derived ceramic matrix composite material provided by the present invention is exemplified. The natural cellulose element-derived ceramic matrix composite material has a layered structure formed by alternating stacking of cellulose elements formed by dissociation of natural materials and reinforcing material zirconium oxide ceramic layers formed in situ on the surface of the cellulose elements; the layered structure presents a natural layered interlocking structure similar to that before the natural cellulose elements are dissociated.
[0020] The layered structure provided by the present invention can cause crack deflection and splitting during the fracture process of the composite material, increase the required fracture energy, thereby improving the overall mechanical properties of the composite material and increasing the bending strength of the material.
[0021] In some embodiments, the source of the cellulose element may include plant shells, preferably coconut shells and nut shells; the length of the cellulose element may be 50-200 um, the width and thickness may both be 10-50 um, and the shape may be a flat spindle. The number of layers of the cellulose element may be designed according to actual needs.
[0022] The cellulose primitives used in the present invention are derived from plant shells containing basic assembly units, i.e., plant shells of flat spindle-shaped units. The main reason for selecting such shells is that these shells can dissociate a large number of primitives with uniform shapes, rather than a messy cellulose solution. The non-uniform cellulose solution cannot achieve uniform wrapping of zirconium hydroxide, and it is difficult to obtain a composite material with good performance.
[0023] In some embodiments, the zirconia ceramic layer may include crystalline zirconia, amorphous zirconia, and a crystalline-amorphous zirconia composite; the thickness of the zirconia ceramic layer may be 1 to 20 μm, preferably 5 to 10 μm. The number of layers of the zirconia ceramic layer may be designed according to actual needs.
[0024] The zirconium oxide ceramics used in the present invention have the ability to transform from gel to ceramic at low temperature. In addition, too much zirconium oxide thickness means that the zirconium content in the original solution must be increased, and too much zirconium will lead to the generation of free zirconium, that is, part of the zirconium hydroxide solid will be directly formed in the solution instead of growing on the cellulose surface, which is not conducive to the improvement of mechanical properties. In addition, too low a zirconium oxide content will also lead to a decrease in mechanical properties.
[0025] In some embodiments, in the natural cellulose-based ceramic composite material, the mass proportion of the natural cellulose base can be 80-20%, and the mass proportion of zirconium oxide can be 20-80%; preferably, the mass proportion of the natural cellulose base can be 80-50%, and the mass proportion of zirconium oxide can be 20-50%; more preferably, the mass proportion of the natural cellulose base is 50%, and the mass proportion of zirconium oxide is 50%. Too much zirconium content will make the composite material more fragile during hot pressing, which is not conducive to material molding; too low zirconium content will lead to insufficient reinforcement phase, and the improvement of mechanical properties is limited.
[0026] The natural cellulose-based ceramic-based composite material provided by the present invention has a flexural strength similar to that of natural coconut shells, etc., and a higher modulus and hardness, and exhibits extremely excellent flame retardant properties. In some embodiments, the flexural strength of the natural cellulose-based ceramic-based composite material can be 60 to 110 MPa, the modulus can be 5 to 20 GPa, and the fracture toughness can be 1 to 3 MPa·m 1 / 2 , the tensile strength can be 10-50 MPa, the hardness can be 0.2-1.5 GPa; the density can be 1.5-2.5 g / cm 3 ; The thermal conductivity in the vertical direction can be 0.25~0.35mm 2 / s, the horizontal thermal conductivity can be 0.1~0.2mm 2 / s.
[0027] The following, combined Figure 1 , exemplarily illustrating the preparation method of the natural cellulose-based element-derived ceramic-based composite material provided by the present invention. The preparation method may include the following steps: (1) crushing the plant shell into centimeter-sized fragments, placing the fragments in a delignification solution containing sodium chlorite, and subjecting them to heat treatment and washing to obtain a natural cellulose elementary solution; (2) mixing the natural cellulose element solution with the zirconium oxychloride octahydrate solution, and adding an ammonia solution to the mixed solution, so that zirconium hydroxide grows in situ on the surface of the natural cellulose element to strengthen the element, and reorganizing the structure of the strengthened element through self-assembly to obtain a natural cellulose element-derived ceramic-based composite material body; (3) subjecting the obtained natural cellulose-based element-derived ceramic-based composite material body to low-temperature hot pressing to obtain the natural cellulose-based element-derived ceramic-based composite material.
[0028] In some embodiments, in step (1), the concentration of sodium chlorite in the delignification liquid containing sodium chlorite can be 5 to 30 wt%, preferably 10 to 20 wt%. Too low a concentration will result in a longer delignification time and poorer effect; too high a concentration will result in waste and will not significantly improve efficiency.
[0029] In some embodiments, in step (1), the heat treatment may be performed in a water bath at a temperature of 40 to 100° C., preferably 60 to 80° C., for 8 to 12 hours. If the temperature is too low, the cellulose elements cannot be peeled off; if the temperature is too high, the liquid will boil, making the operation difficult. At the same time, a good peeling effect can be ensured by controlling the appropriate heat treatment temperature.
[0030] In some embodiments, in step (1), the concentration of the natural cellulose base solution may be 1 to 50 g / L, preferably 2.5 to 5 g / L.
[0031] In some embodiments, in step (2), the mass ratio of the natural cellulose unit to the theoretically generated zirconium oxide can be controlled to be 1: (0.25-4) (corresponding to the mass ratio of the natural cellulose unit to zirconium oxychloride octahydrate is 1: 0.655-10.48), preferably 1: 1. If the zirconium content is too low, the mechanical properties of the reconstituted composite material will be poor, especially the bending strength will be poor; if the zirconium content is too high, some free zirconium hydroxide will appear in the strengthening process, rather than in-situ grown zirconium hydroxide, which will eventually have a negative impact on the performance of the composite material.
[0032] In some embodiments, in step (2), the concentration of the aqueous ammonia solution can be 0.2-2 wt %, preferably 0.5-1 wt %, and the pH value of the mixed solution can be controlled to be 10-12.
[0033] In some embodiments, in step (2), the method for reorganizing the elementary structure may include suction assembly, evaporation self-assembly, shear force self-assembly, pressure assembly, and ice template method.
[0034] In some embodiments, in step (3), the temperature and pressure of the low temperature hot pressing may be 60-200° C. and 50-500 MPa, respectively, preferably 120-160° C. and 150-300 MPa, and the time of the low temperature hot pressing may be 1-24 h.
[0035] Zirconium hydroxide grows in situ on the surface of the element under the action of pH value to form a reinforcement coating, and forms a zirconium oxide reinforcement after hot pressing. Zirconium oxide has good contact with the surface of the element. After hot pressing, the zirconium oxides and the zirconium oxides and the element matrix are in close contact and good interface contact, so that the obtained material has good mechanical properties. The recombinant composite material finally prepared by the present invention has the same or similar structure as the natural material and exhibits similar bending strength. At the same time, due to the presence of zirconium oxide, it has a higher modulus, hardness and excellent flame retardant properties.
[0036] The natural cellulose-based element-derived ceramic-based composite material obtained by the preparation method provided by the present invention is applied to flame retardancy, explosion prevention, biomedicine and the like.
[0037] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0038] Example 1
[0039] The preparation method of the natural cellulose-based element-derived ceramic-based composite material (recombinant CSU@Zr composite material) provided in this embodiment comprises the following steps: (1) 40 g of sodium chlorite (NaClO 2 ) was added to deionized water and stirred until it was completely dissolved, 10 g of coconut shell fragments were added, and the mixture was placed in a water bath at 80°C and stirred for 10 h until the coconut shell was completely dissociated; the dissociated coconut shell unit (CSU) was washed with deionized water until the supernatant was colorless, and then the concentration was adjusted to 50 mg / mL with deionized water; (2) taking 20 ml of the 50 mg / ml CSU solution obtained in step (1) and adding it to 400 ml of deionized water, stirring evenly, adding 2.62 g of zirconium oxychloride octahydrate, stirring for 10 min, and then dropping 0.5% ammonia solution into the solution until the pH value is equal to 10; adding a double layer of filter paper into a Buchner funnel, adding the obtained mixed solution into the funnel, and self-assembling under the assistance of vacuum filtration to obtain a natural cellulose-based element-derived ceramic-based composite body; (3) The natural cellulose-based ceramic-based composite material body obtained in step (2) is placed in a mold, and hot-pressed at 140° C. and a pressure of 200 MPa for 4 h to obtain a recombinant CSU@Zr composite material.
[0040] The recombinant coconut shell material CSU@Zr composite material prepared in Example 1 was tested, and it was found that the flexural strength was 102.1 MPa, the modulus was 14.1 GPa, and the fracture toughness was 1.6 MPa·m 1 / 2 , tensile strength is 35MPa, density is 1.99g / cm 3 ; Thermal conductivity is 0.29mm 2 / s (vertical direction) and 0.16mm 2 / s (horizontal direction). The difference in thermal conductivity in the two directions is due to the anisotropy of its structure.
[0041] Comparative Example 1
[0042] The preparation method of the composite material (non-in-situ grown recombinant CSU / Zr composite material) provided in this comparative example 1 refers to that in Example 1, the main difference is that: In step (2), 2.62 g zirconium oxychloride octahydrate was first added to deionized water, and after stirring for 10 min, 0.5% ammonia solution was added dropwise to the solution until the pH value was equal to 10, and then 20 ml of 50 mg / ml CSU solution was added. After stirring for 1 h, subsequent steps such as filtration were performed.
[0043] The recombinant coconut shell material CSU / Zr prepared in Comparative Example 1 was tested, and the results showed that the flexural strength was 69.0 MPa, the modulus was 6.7 GPa, and the fracture toughness was 1.0 MPa·m 1 / 2 , the tensile strength is 24.1MPa.
[0044] Comparative Example 2
[0045] The preparation method of the composite material (CSU / pZr composite material reconstituted from a zirconium oxide powder mixture) provided in this comparative example 2 refers to that in Example 1, the main difference is that: In step (2), 20 ml of 50 mg / ml CSU solution was added to 400 ml of deionized water, and after stirring evenly, 1 g of zirconium oxide powder was added. After stirring for 10 min, 0.5% ammonia solution was added dropwise to the solution until the pH value was equal to 10. After stirring for 1 h, subsequent filtration and other steps were performed.
[0046] The recombinant coconut shell material CSU / pZr prepared in Comparative Example 2 was tested, and the results showed that the flexural strength was 63.9 MPa, the modulus was 9.3 GPa, and the fracture toughness was 1.4 MPa·m 1 / 2 , the tensile strength is 22.1MPa.
[0047] Comparative Example 3
[0048] The preparation method of the pure coconut shell element recombinant material provided in this comparative example comprises the following steps: (1) 40 g of sodium chlorite (NaClO 2 ) was added to deionized water and stirred until it was completely dissolved, 10 g of coconut shell fragments were added, and the mixture was placed in a water bath at 80°C and stirred for 10 h until the coconut shell was completely dissociated; the dissociated coconut shell element was washed with deionized water until the supernatant was colorless, and then the concentration was adjusted to 50 mg / ml with deionized water; (2) Add a double layer of filter paper to a Buchner funnel, add 40 ml of the elementary solution into the funnel, and perform self-assembly with the assistance of vacuum filtration to obtain a pure coconut shell elementary recombinant material blank; (3) The pure coconut shell-based recombinant material blank is placed in a mold and hot-pressed at 140° C. and a pressure of 200 MPa for 4 h to obtain the pure coconut shell-based recombinant material.
[0049] The recombinant coconut shell material CSU prepared in comparative example 3 was tested, and the results showed that the flexural strength was 48.2 MPa, the modulus was 3.6 GPa, and the fracture toughness was 1.0 MPa·m 1 / 2 , the tensile strength is 18.7MPa.
[0050] Comparative Example 4
[0051] The preparation method of the initial coconut shell CS provided in this comparative example comprises the following steps: The outer and inner surfaces of the coconut shell are mechanically polished to remove surface impurities, and then processed into samples of a certain size using a cutting machine.
[0052] The initial coconut shell CS prepared in comparative example 4 was tested, and the results showed that the flexural strength was 98.0 MPa, the modulus was 4.0 GPa, and the fracture toughness was 2.2 MPa·m 1 / 2 , the tensile strength is 59.0MPa.
[0053] Figure 2 The cross-section and surface SEM images of the initial coconut shell used in Example 1. The left image is a cross-sectional structure perpendicular to the coconut shell, and the right image is a surface structure parallel to the coconut shell. It can be seen from the figure that the coconut shell is assembled layer by layer from rod-shaped primitives and has a special directional structure.
[0054] Figure 3 The SEM images of the coconut shell cellulose primitives after dissociation (left picture) and coconut shell cellulose primitives after zirconium oxide deposition (right picture) used in Example 1. It can be seen from the figure that the coconut shell primitives are successfully dissociated and evenly dispersed as independent primitive monomers.
[0055] Figure 4 This is the SEM image of the cellulose base element surface strengthened by the zirconium layer. The proportions from left to right are CSU:ZrO 2 =4:1, 2:1 and 1:1, and the element distribution diagram is shown below. It can be seen from the figure that the zirconium layer grows evenly on the surface of the coconut shell element.
[0056] Figure 5 The CT reconstruction images of the recombinant material CSU@Zr (left) and the natural coconut shell material (right) prepared in Example 1. It can be seen from the figure that the two have similar structures and are blocks assembled from primitives.
[0057] Figure 6 The cross-sectional SEM image and element distribution diagram of the recombinant material CSU@Zr prepared in Example 1. As can be seen from the figure, the recombinant material prepared in Example 1 is composed of alternating stacking of primitives and zirconium layers, which indicates that the strengthened primitives can be reorganized into an ordered structure by directional assembly.
[0058] Figure 7 The bending strength comparison diagram of the materials prepared in Example 1 and Comparative Examples 1-4, wherein: CS is the initial natural coconut shell, CSU is the pure coconut shell element recombinant material, CSU / pZr is the recombinant material of coconut shell element and zirconium oxide ceramic powder, CSU / Zr is the recombinant material of coconut shell element and zirconium oxide grown ex situ, and CSU@Zr is the recombinant material after the zirconium layer is grown in situ on the element surface. It can be seen from the figure that the recombinant material prepared in Example 1 has similar bending strength to the initial coconut shell.
[0059] Figure 8 The figure is a comparison of the moduli of the materials prepared in Example 1 and Comparative Examples 1 to 4. As can be seen from the figure, the recombined material prepared in Example 1 exhibits a higher modulus.
[0060] Fig. 9 The cross-sectional SEM images of the materials prepared in Example 1 and Comparative Examples 1 to 4 show that the CSU@Zr recombinant material has its primitives torn apart during the fracture process, indicating good interface contact between the reinforcement and the primitives, while the other recombinant materials show complete primitive pullout, indicating poor cross-sectional contact.
[0061] Fig.10 The hardness comparison diagram of the materials prepared in Example 1 and Comparative Examples 1-4 is shown in FIG. As can be seen from the figure, the recombined materials prepared in the examples exhibit relatively high hardness.
[0062] Fig.11This is a comparison chart of the heat release rate (HRR) of the flame retardant test of coconut shell and CSU@Zr. As can be seen from the figure, the coconut shell group has an obvious peak, indicating that it can be ignited, while the recombinant material has no obvious peak, indicating that it cannot be ignited, showing excellent flame retardant properties.
[0063] Comparative Example 5
[0064] The preparation method of the composite material (in-situ grown heavy CSU / Zr composite material with high zirconium content) provided in this comparative example 1 refers to that of example 1, with the main difference being that in step (2), the amount of zirconium oxychloride octahydrate added is 13.1 g.
[0065] The material prepared in Comparative Example 5 is very easy to break during the hot pressing process, mainly because its inorganic content is too high and it is difficult to form at low temperature.
[0066] Comparative Example 6
[0067] The preparation method of the composite material (in-situ grown heavy CSU / Zr composite material with low zirconium content) provided in this comparative example refers to that of Example 1, with the main difference being that in step (2), the amount of zirconium oxychloride octahydrate added is 0.44 g.
[0068] The flexural strength of Comparative Example 6 is 50 MPa, which is significantly lower than that of Example 1.
[0069] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A natural cellulose-based ceramic-based composite material, characterized in that: The natural cellulose element-derived ceramic matrix composite material has a layered structure formed by alternating stacking of cellulose elements formed by dissociation of natural materials and zirconium oxide ceramic layers of reinforcing materials formed in situ on the surface of the cellulose elements; the layered structure presents a natural layered interlocking structure similar to that of natural cellulose elements before dissociation; The source of the cellulose base element includes plant shells; the zirconia ceramic layer includes crystalline zirconia, amorphous zirconia and crystalline-amorphous zirconia composite; The mass proportion of the natural cellulose unit is 80-20%, and the mass proportion of zirconium oxide is 20-80%.
2. The natural cellulose-based ceramic-based composite material according to claim 1, characterized in that: In the natural cellulose element-derived ceramic-based composite material, the length of the cellulose element is 50-200 μm, and the width and thickness are both 10-50 μm; the thickness of the zirconia ceramic layer is 1-20 μm.
3. The natural cellulose-based ceramic-based composite material according to claim 1 or 2, characterized in that: The natural cellulose-based element-derived ceramic-based composite material has a flexural strength of 60 to 110 MPa, a modulus of 5 to 20 GPa, and a fracture toughness of 1 to 3 MPa·m 1 / 2 , tensile strength is 10~50MPa, and hardness is 0.2~1.5GPa.
4. A method for preparing a natural cellulose-based element-derived ceramic-based composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) placing plant shell fragments in a delignification solution containing sodium chlorite, and subjecting them to heat treatment and washing to obtain a natural cellulose base solution; (2) mixing the natural cellulose element solution with the zirconium oxychloride octahydrate solution, stirring, adjusting the pH, and reorganizing the element structure to obtain a natural cellulose element-derived ceramic-based composite material body; (3) subjecting the obtained natural cellulose-based element-derived ceramic-based composite material body to low-temperature hot pressing to obtain the natural cellulose-based element-derived ceramic-based composite material.
5. The preparation method according to claim 4, characterized in that: In step (1), the concentration of sodium chlorite in the delignification liquid containing sodium chlorite is 5 to 30 wt %, preferably 10 to 20 wt %.
6. The preparation method according to claim 4 or 5, characterized in that: In step (1), the concentration of the natural cellulose base solution is 1 to 50 g / L, preferably 2.5 to 5 g / L.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (2), the mass ratio of the natural cellulose unit to the theoretically generated zirconium oxide is 1:(0.25-4), preferably 1:
1.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (2), ammonia water is added to adjust the pH value. The concentration of the ammonia water solution is 0.2-2 wt %, preferably 0.5-1 wt %, and the pH value of the mixed solution is controlled to be 10-12.
9. The preparation method according to any one of claims 4 to 8, characterized in that: In step (2), the methods for reorganizing the elementary structures include suction assembly, evaporation self-assembly, shear force self-assembly, pressure assembly, and ice template method.
10. The preparation method according to any one of claims 4 to 9, characterized in that: In step (3), the temperature and pressure of the low-temperature hot pressing are 60-200° C. and 50-500 MPa, respectively, preferably 120-160° C. and 150-300 MPa, and the time of the low-temperature hot pressing can be 1-24 hours.